STRATEGI PSIKOEDUKASI INKLUSI: SEMINAR ORIENTASI MOBILITAS TUNANETRA BAGI WARGA BINAAN PEMASYARAKATAN DI LAPAS KELAS III RANGKASBITUNG - Fitriani, Laelatul; Al-Anshori, Dody Bakhtiar; Mulia, Dedi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
ABSTRACT The "Impact Internship" program aims to create inclusive spaces in correctional institutions. This study describes the implementation of a Mobility Orientation seminar for inmates under supervision at Rangkasbitung Class III Correctional Institution. The main problem identified was inmates' low understanding of the function of the guide block facilities available in the prison. The method used was a qualitative descriptive approach through lecture-based educational activities and direct instruction. This approach was chosen because it has proven effective in improving conceptual understanding and practical skills in mobility orientation learning. The results of the activity showed a significant increase in participants' understanding of the nature of blindness and their ability to practice the use of guide blocks in simple ways. This activity successfully fostered empathy and understanding of inclusion as an effort to social reintegrate inmates.